Using mHealth strategies in a Diabetes Management Program to improve the quality of care in Argentina: Study design and baseline data. Issue 6 (December 2018) - Santero, Marilina; Morelli, Daniela; Nejamis, Analía; Gibbons, Luz; Irazola, Vilma; Beratarrechea, Andrea
Highlights: In Argentina diabetes represents a significant public health problem. mHealth interventions constitute a promise for health care delivery. A multi-component intervention targeting diabetic patients has been implemented. It may help to individualize therapeutic goals according to each person's needs. It allows to draw and know the epidemiological profile of people with diabetes. Abstract: Aim: To evaluate the one-year post effect of the implementation of a diabetes program that includes mHealth interventions on the quality of diabetic care in public primary care centers. Method: It is a quasi-experimental study with outcome measurements at baseline, 6 and 12 months. The program includes primary care team training, a diabetes registry with a decision support tool in an app. and text messages for patients. Results: At baseline, 947 patients were included in the registry, 62.3% women with a mean age of 53.6 ± 11.5 years and 92% with type 2 diabetes. Common comorbidities were hypertension (61.3%) and obesity (59%). Only 16.9% had one HbA1c and 48.9% a cholesterol lab in the last year, 61.9% were screened for diabetic peripheral neuropathy, and 29.0% had one eye exam in the previous year. With respect to blood sugar, lipid and blood pressure control: 44.4% of those with HbA1c measurements had levels ≥8%, total cholesterol was over 200 mg/dL in 40.6% and 48.2% had uncontrolled blood pressure values. Conclusion: Patients with diabetes received a low quality of care at public primary care clinics. A diabetes registry allowed us to draw an epidemiological profile of diabetic patients and determine the quality of care provided.